THE MARRIAGE OF ʿĀISHAH (RA) IN THE PERSPECTIVE OF MAQĀṢID AL-SHARĪʿAH: A HISTORICAL AND NORMATIVE ANALYSIS OF THE OBJECTIVES OF ISLAMIC LAW - Abdurrasyid Ridha; Adang Djumhur Salikin; Achmad Kholiq; Sugianto Sugianto (Faculty of Law, Universitas Pekalongan, 2023)
This paper analyzes the marriage of the Prophet Muḥammad (peace be upon him) to Aishah (may Allah be pleased with her) within the framework of maqāṣid al-sharīʿah, emphasizing the historical, normative, and educational dimensions of the event. Modern debates that highlight the issue of ʿĀishah’s age often stem from a literalist reading detached from the maqāṣid-based context of Islamic law. Through a qualitative literature study of classical sources such as al-Sīrah al-Nabawiyyah, al-Muwāfaqāt by al-Shāṭibī, and Maqāṣid al-Sharīʿah al-Islāmiyyah by Ibn ʿĀshūr, this article finds that the marriage carries broad legal dimensions: the protection of lineage (ḥifẓ al-nasl), preservation of religion (ḥifẓ al-dīn), education of the ummah (taʿlīm al-ummah), and the formation of Islamic family ethics. Methodologically, this study employs a maqāṣidī-historical approach, using qualitative analysis of both texts and the 7th-century Arabian social context. The findings suggest that the marriage of ʿĀishah was not merely a historical fact but a sharīʿah instrument for safeguarding moral order and the epistemology of Islamic law. A maqāṣid-based understanding helps to avoid ahistorical interpretations while reinforcing the relevance of Islamic family ethics in the modern era.